Why nations fail : the origins of power, prosperity and poverty - Acemoglu, Daron; Robinson, James A. (London : Profile, 2012)
This book is about the huge differences in incomes and standards of living that separate the rich countries of the world, such as the United States, Great Britain, and Germany, from the poor, such as those in sub-Saharan Africa, Central America, and South Asia.
Bibliography: p. [483]-509. - Includes index.
mck22/08/22
Loans
Keywords: Institutional economics; Economic anthropology; Economic history; Failed states